Al-Turāth al-‘Ilmī al-Islāmī bi Indūnīsiyā: Dirāsat fī Tafsīray Malja’ al-Ṭālibīn wa Tamshīyāh al-Muslimīn li al-Shaykh al-Ḥajj Aḥmad Sanūsī - Hasan Husain Umar (Studia Islamika, 2001)
Haji Ahmad Sanusi, the main figure with whom this article is concerned, is an activist and a productive writer. Born in Sukabumi from a Kyai family, he spent the first 20 years of his life in West Java, moving from one pesantren to another in pursuit of religious knowledge. He spent the next 5 years in Mecca, studying under the supervision of famous scholars. It was during his stay in Mecca that he became associated with not only the intellectual network in the Islamic world but also with the Ind (political) world. He became d supporter of Sarekat Islam (SI) and wrote a book, his first book, to defend it.DOI: 10.15408/sdi.v8i1.698